87.6k views
5 votes
Just solve it for me no need to explain

Just solve it for me no need to explain-example-1
User IamPolaris
by
5.2k points

2 Answers

6 votes

Answer:

Explanation:

Just solve it for me no need to explain-example-1
User Able
by
5.3k points
6 votes

Answer: -5/21.

Explanation:


(2)/(5)*[(-3)/(7) +((-1)/(6))]=(2)/(5) *(-(3)/(7) -(1)/(6)) =(2)/(5)*(-(3*6+1*7))/(7*6) )=(2)/(5)*(-(18+7)/(42))=(2)/(5)*(-(25)/(42))=-(5)/(21) .

Good luck an' have a nice day!

User Michael Williamson
by
4.7k points